Decreased Diffusion in Central Pontine Myelinolysis - Cramer, Steven C. (AJNR Am J Neuroradiol, 2001)
Summary: Two patients with central pontine myelinolysis (CPM) were studied with diffusion-weighted MR imaging 1 week after onset of tetraplegia. In both patients, affected white matter showed hyperintensity on diffusion-weighted images associated with a decrease in apparent diffusion coefficient (ADC) values. In one patient studied serially, ADC values normalized by 3 weeks after tetraplegia. Early in the clinical course, diagnosis of CPM can sometimes be difficult. Hyperintensity on diffusion-weighted images may therefore have diagnostic utility. Decreased lesional ADC values support the notion that CPM is a consequence of relative intracellular hypotonicity.